2015
DOI: 10.15376/biores.10.4.6872-6885
|View full text |Cite
|
Sign up to set email alerts
|

Biocomposites Based on Rice Husk Flour and Recycled Polymer Blend: Effects of Interfacial Modification and High Fibre Loading

Abstract: Biocomposites were prepared with rice husk flour (RHF) (raw and alkalitreated) in a recycled polymer blend (RPB) using a co-rotating twin screw extruder. Modifications to the composite were carried out through fibre surface treatment with 4 wt.% sodium hydroxide (NaOH) and 3 wt.% maleic anhydride polyethylene (MAPE) coupling agent. Fourier transform infrared (FTIR) analyses of raw and NaOH-treated RHF were performed. The effects of the interfacial modification (MAPE or/and NaOH) and filler loading (50 to 80 wt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 23 publications
4
38
0
Order By: Relevance
“…The increase in tensile strength and elastic modulus was attributed to the enhanced interfacial interaction and bonding between the hydrophobic rTPB matrix and the hydrophilic fillers via the mechanical interlocking induced by alkali treatment on the surface of RH fibers, and also to the interfacial modification by the addition of a MAPE coupling agent. The improvement of mechanical interlocking by the alkali treatment could be explained with the facts where: (1) the NaOH treatment increased the surface roughness of RH and promoted the fibre fibrillation, as observed in our previous work (Chen et al 2015b);and (2) when the fibre surface is rough, the mechanical interlocking could occur to a greater extent (Pickering et al 2016). On the other hand, the latter reduction in tensile strength and elastic modulus was attributed to the insufficient filler-matrix adhesion and interaction for the higher difference ratio of polymer matrix: filler in the rTPB/RH, which was about one fifth, as indicated by the SEM micrograph ( Fig.…”
Section: Tensile Propertiessupporting
confidence: 64%
See 1 more Smart Citation
“…The increase in tensile strength and elastic modulus was attributed to the enhanced interfacial interaction and bonding between the hydrophobic rTPB matrix and the hydrophilic fillers via the mechanical interlocking induced by alkali treatment on the surface of RH fibers, and also to the interfacial modification by the addition of a MAPE coupling agent. The improvement of mechanical interlocking by the alkali treatment could be explained with the facts where: (1) the NaOH treatment increased the surface roughness of RH and promoted the fibre fibrillation, as observed in our previous work (Chen et al 2015b);and (2) when the fibre surface is rough, the mechanical interlocking could occur to a greater extent (Pickering et al 2016). On the other hand, the latter reduction in tensile strength and elastic modulus was attributed to the insufficient filler-matrix adhesion and interaction for the higher difference ratio of polymer matrix: filler in the rTPB/RH, which was about one fifth, as indicated by the SEM micrograph ( Fig.…”
Section: Tensile Propertiessupporting
confidence: 64%
“…6(b), the strain at break of the composites showed a negative correlation with the RH content as compared with the neat rTPB. This trend was as estimated because the RH is a type of stiff organic filler that possesses a brittle nature, and hence, the incorporation of RH in a high filler loading (more than 50 wt%) tended to decrease the ductility characteristic of the polymer matrix (Chen et al 2015b). Therefore, the strain at break of the composite decreased with the different rTPB/RH compositions, corresponding to the following order: 100/0 < 50/50 < 40/60 < 30/70 < 20/80 (wt%).…”
Section: Tensile Propertiesmentioning
confidence: 85%
“…The rice husk BCB treated with NaOH at 70% wt shown the highest tensile and modulus strength. Although the Scanning electron microscope showed a rough surface of the treated samples, but the fibre treatment proved effective [90].…”
Section: Rice Fibre Bio-composite Boardsmentioning
confidence: 92%
“…Despite the issue of surface interaction with polymer matrix, some previous studies reported that rice husk BCB could be used in furniture and interior fitments manufacturing, although, the physical and mechanical properties of the boards were lower than those of the BCB made from wood particles [83][84][85]. Further research was carried out by using a fibre surface treatment with 4% wt of NaOH and 3% wt of Maleic anhydride polyethylene (MAPE) coupling agent [90]. Fourier transform infrared (FTIR) analysis was performed on the treated and untreated rice husk fibre.…”
Section: Rice Fibre Bio-composite Boardsmentioning
confidence: 99%
“…Reducing moisture absorption of natural fibers is an effective way to modify the mechanical properties of these materials. Researchers have employed a number of fiber surface treatments to reduce moisture sensitivity of natural fibers . The treatments aim to chemically modify the surface of the fiber to reduce moisture absorption.…”
Section: Introductionmentioning
confidence: 99%